Effects of Chlorhexidine and Sodium Hypochlorite on the Setting Time of Calcium-Enriched Mixture Cement - Frough Reyhani, Mohammad; Ghasemi, Negin; Shakouie, Sahar; Rahimi, Saeed; Salem Milani, Amin; Ranjbar, Babak (Iranian Endodontic Journal, 2015)
Introduction: The aim of the present study was to evaluate whether adding 2% chlorhexidine (CHX) and 2.6% sodium hypochlorite (NaOCl) to calcium-enriched mixture (CEM) cement would affect its setting time (ST), or not. Methods and Materials: In this study, the setting time of CEM cement was evaluated in three groups (n=9) as follows: group 1; CEM cement, group 2; CEM cement+2% CHX and group 3; CEM cement+2.6% NaOCl. Then the mean values of ST were calculated and the Kolmogorov-Smirnov test was used to evaluate the normal distribution of data. The Kruskal-Wallis and Mann-Whitney U tests were used for statistical analysis. Statistical significance was set at 0.05. Results: The mean ST for groups 1, 2 and 3 were 105, 120 and 220 min, respectively. There was a significant increase in the duration of ST in group 3 (NaOCl) in comparison with the two other groups (P<0.05). Conclusion: NaOCl significantly increased the ST of CEM cement, whereas chlorhexidine did not alter the ST. Keywords: Calcium-Enriched Mixture; CEM Cement; Chlorhexidine; Setting Time; Sodium Hypochlorite